The menstrual cycle and sports performance - Fischetto, G.; Sax, A. (New Studies in Athletics, 2013)
ABSTRACT Since the first modern Olympic Games there has been increased female participation in high-level sport competitions and this growth has been exponential in the last 60 years. Among the issues linked to women in sport is the role of the menstrual cycle in performance. While a stable endocrinological condition is observed in males, the large variations between the follicular phase and luteal phase in women's cycles make it difficult to identify a comparable stable condition, which has practical implications for training and competition. Moreover, there are a number of menstrual disorders that can affect and/or are linked to intensive physical training. In this article, the authors review the existing literature on all key aspects of the menstrual cycle and sport performance. Their aim is to support coaches and others working to improve the performance of female athletes by providing short overviews of the following areas: a) the menstrual cycle, b) physiologic and metabolic variations in the menstrual cycle, c) adaptation of training to menstrual phases, d) menstrual disorders in athletes and the Female Athlete Triad, e) Dysmen-orrhoea in athletes, f) oral contraceptives and performance.